2019
DOI: 10.3390/nano9040644
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Electrospun Fiber Mat Thickness and Support Method on Cell Morphology

Abstract: Electrospun fiber mats (EFMs) are highly versatile biomaterials used in a myriad of biomedical applications. Whereas some facets of EFMs are well studied and can be highly tuned (e.g., pore size, fiber diameter, etc.), other features are under characterized. For example, although substrate mechanics have been explored by several groups, most studies rely on Young’s modulus alone as a characterization variable. The influence of fiber mat thickness and the effect of supports are variables that are often not cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Young’s modulus (E) of the electrospun pure r-PET, r-PSF mats, containing different SF amounts is shown in Figure 4 . Young´s modulus is attributed to the strength of the interaction between fibers within the material that does not significantly depend on its thickness [ 89 ]. It was observed that increasing SF content in r-PSF samples increases the E. Similar behavior was reported by Gobin et al [ 90 ], which attributed these changes to more numerous interactions of SF, with presented chitosan in the form of strong molecular hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Young’s modulus (E) of the electrospun pure r-PET, r-PSF mats, containing different SF amounts is shown in Figure 4 . Young´s modulus is attributed to the strength of the interaction between fibers within the material that does not significantly depend on its thickness [ 89 ]. It was observed that increasing SF content in r-PSF samples increases the E. Similar behavior was reported by Gobin et al [ 90 ], which attributed these changes to more numerous interactions of SF, with presented chitosan in the form of strong molecular hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…The published results, as well as opinions on this topic, seem clear. Silk is not considered a polymer with antibacterial activity [ 89 , 103 ]. On the other side, there have been published studies that have shown that the antibacterial activity of polymers in different forms is influenced by many factors related to its preparation, processing [ 104 ], possibly mixing with other polymers [ 50 , 105 ] or active molecules, drugs, and biocides [ 106 , 107 , 108 ].…”
Section: Resultsmentioning
confidence: 99%
“…GBM cells display high sensitivity to their mechanical microenvironment. For example, we have shown that U87 GBM cells grown on 50 µm thick electrospun fiber mats 35 or patient-derived GBM cells cultured in <25 µm thick hydrogels 36 are sensitive to the mechanics of their underlying supports. GBM cells also increase migration in response to low linear flow rates (<1 µm/s) 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Packing density of an electrospun material has been shown to play a large role on the properties of electrospun materials in comparison to mat thickness (Leung et al, 2010 ). One study observed the effects of electrospun polycaprolactone fiber mat thickness on indentation modulus, and found that an increase in mat thickness resulted in an increase in indentation modulus in supported mats (Calhoun et al, 2019 ). Additionally, a 1.5x increase in Young's modulus was observed in unsupported polycaprolactone mats when comparing a 50 um thick mat to a 200 um thick mat.…”
Section: Introductionmentioning
confidence: 99%